Targeting c-MYC: a potential non-hormonal therapeutic approach for endometriosis treatment - Nothnick, Warren B.; Arachchige, Sachith Polpitiya; Minchella, Paige; Stephens, Edward B.; Graham, Amanda (Frontiers in Cell and Developmental Biology, 2023)
Endometriosis is a benign gynecological disease in which eutopic endometrial tissue composed of glands and stroma grow within the pelvic cavity. The disease affects females of reproductive age and is characterized by pelvic pain, infertility and reduced quality of life. The majority of pharmacologic treatment modalities for endometriosis focus on suppression of estradiol production and/or action; an approach associated with adverse side effects. c-MYC is elevated in eutopic endometrium and endometriotic lesion tissue in patients with endometriosis and the disease shares many similar pathological characteristics with that of endometrial carcinoma. While targeting of c-MYC with Omomyc has recently gained substantial interest in the field of cancer research, there has been no recent attempt to evaluate the potential utility in targeting c-MYC for endometriosis treatment. The following perspective article compares the similarities between endometriosis and endometrial cancer and presents preliminary data suggesting that targeting c-MYC with Omomyc reduces endometriotic cell proliferation and viability in vitro. Future application of targeting c-MYC in endometriosis treatment and potential pros and cons are then discussed.